Przedmiot i zakres planowania inwestycji na szczeblu centralnym. Doświadczenia i postulaty w warunkach polskich - Tomidajewicz, Janusz J. (Wydział Prawa i Administracji UAM, 1975)
The aim of the paper is to answer the following questions: 1) What should be the subject of investment decisions at the central (national) level? 2) What methods should be used to reach investment decisions of the central level? 3) What informations can be supplied by the clufer to other decision making levels? The answers to the above questions deal separately with each major element of the investment decision, i. e. with the scope of investment its sectoral structure, techniques of production, the role of the time- actor in the investment decisions and the location of investment activities. The main conclusions of the paper are the following: In order to implement the central economic preferences it is necessary to make macro-economic decisions in all the above-mentioned investment problems. However, in View of the scope of informations and the possibilities of their utilization at the central level, these decisions should only deal with the (key aggregates. At this level it is not necessary to make (individual investment decisions.
Subject and Methods of Investment Decisions at the National Level (The Polish Experience)